Two-scale Convergence and Homogenization for a Class of Quasilinear Elliptic Equations (Journal of Partial Differential Equations, 1996)
By use of Fourier analysis techniques, we obtain some new properties of the almost-periodic functions and extend the two-scale convergence method in the homogenization theory to the case of almost-periodic oscillations. Then, we use some new techniques to study the homogenization for quasilinear elliptic equations with almostperiodic coefficients: div a(x,x/ε, u, Du) = f(x) in Ω and obtain the weak convergence and corrector result.
Keywords: Partial differential equations; homogenization; weak convergence; almost-periodic; two-scale convergence